2022
DOI: 10.1037/amp0001005
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness before and during the COVID-19 pandemic: A systematic review with meta-analysis.

Abstract: The COVID-19 pandemic and measures aimed at its mitigation, such as physical distancing, have been discussed as risk factors for loneliness, which increases the risk of premature mortality and mental and physical health conditions. To ascertain whether loneliness has increased since the start of the pandemic, this study aimed to narratively and statistically synthesize relevant high-quality primary studies. This systematic review with meta-analysis was registered at PROSPERO (ID CRD42021246771). Searched datab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
152
4
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 277 publications
(207 citation statements)
references
References 73 publications
4
152
4
4
Order By: Relevance
“…May), COVID-19 associated infections [deaths] reached 3,638,504 [87,135], and 32,961,750 people (about 39.29% of the German population) received at least one vaccination (Dong et al, 2020). 1 This extraordinary situation showed an impact on various psychological health outcomes, including increased loneliness (i.e., painful subjective feelings of isolation and with this an indicator of social well-being; Ellis et al, 2020;Huxhold and Tesch-Römer, 2021;Ernst et al, 2022), decreased life satisfaction (i.e., the cognitive evaluation of one's own subjective well-being; Zacher and Rudolph, 2021b), and increased psychological distress with anxiety and depressive symptoms (Arslan et al, 2021; for an overview see Hossain et al, 2020). While these findings indicate substantial COVID-19-related psychological distress, researchers also reported heterogeneous results (Ernst et al, 2022) or resilience (Luchetti et al, 2020), motivating research on potential vulnerability and protective factors.…”
Section: Psychological Effects Of Covid-19mentioning
confidence: 99%
“…May), COVID-19 associated infections [deaths] reached 3,638,504 [87,135], and 32,961,750 people (about 39.29% of the German population) received at least one vaccination (Dong et al, 2020). 1 This extraordinary situation showed an impact on various psychological health outcomes, including increased loneliness (i.e., painful subjective feelings of isolation and with this an indicator of social well-being; Ellis et al, 2020;Huxhold and Tesch-Römer, 2021;Ernst et al, 2022), decreased life satisfaction (i.e., the cognitive evaluation of one's own subjective well-being; Zacher and Rudolph, 2021b), and increased psychological distress with anxiety and depressive symptoms (Arslan et al, 2021; for an overview see Hossain et al, 2020). While these findings indicate substantial COVID-19-related psychological distress, researchers also reported heterogeneous results (Ernst et al, 2022) or resilience (Luchetti et al, 2020), motivating research on potential vulnerability and protective factors.…”
Section: Psychological Effects Of Covid-19mentioning
confidence: 99%
“…It consists of 20 items with a fourpoint scale ranging from 1 (Never) to 4 (Often). The estimates of internal consistency range from 0.88-0.93, as found in various studies [10][11][12][13][14][21][22][23][24][25]. Two South African studies reported acceptable reliability (0.81 and 0.92) for the UCLA-20 when used with student samples [46,47].…”
Section: Instrumentsmentioning
confidence: 73%
“…The importance of conducting studies on loneliness has been highlighted by pre-pandemic studies, where loneliness was found to be associated with adverse mental health outcomes, including depression and anxiety, and high mortality [11]. Similar results were found during the pandemic.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations